The Changing Prevalence of Non-Alcoholic Fatty Liver Disease (NAFLD) in Turkey in the Last Decade - Değertekin, Bülent; Tozun, Nurdan; Demir, Figen; Söylemez, Gizem; Parkan, Şirin; Gürtay, Ezgi; Mutlu, Deniz; Toraman, Meltem; Seymenoğlu, Tolga Hayrettin (Turkish Journal of Gastroenterology, 2021)
Background/Aims: The true prevalence of Non-Alcoholic Fatty Liver Disease (NAFLD) is unknown in Turkey due to a lack of population-based studies. The aim of this study was (i) to determine the overall and region-specific prevalence of NAFLD in Turkey; (ii) to analyze the factors associated with the prevalence; and (iii) to determine the nationwide change in the prevalence of NAFLD in the last decade.Materials and methods: The 10-year data (2007 to 2016) of 113,239 apparently healthy subjects visiting the check-up clinics of Acibadem Hospitals Group were retrospectively analyzed. A subgroup of patients (n=8120) statistically representing the bigger cohort were selected. The prevalence was analyzed according to ultrasound findings, age, sex, body mass index (BMI), geographical region, and time periods trisected as 2007-2010, 2011-2013 and 2014-2016. Results: The overall prevalence of NAFLD in Turkey was found to be 48.3%. It was highest among people >50 years of age (65.6%), male sex (64.0%), with a BMI>25 kg/m2 (63.5%) and in Central and Eastern Anatolia regions (57.1% and 55.7%, respectively). The prevalence of NAFLD was 43.5% between 2007-2010, 47.6% between 2011-2013 and 53.1% between 2014-2016 and the rate of increase was 22%. Multivariate analysis showed that male sex, serum alanine aminotransferase (ALT) level, older age, BMI, type-II diabetes mellitus, hypertension and dyslipidemia were independent factors associated with NAFLD. Conclusion: NAFLD is a highly prevalent disease affecting almost half of the Turkish population (48.3%). We are faced with a dramatic increase in NAFLD prevalence in the past 10 years.